Pre-dispersing process of organo-montmorillonite nanofiller: influence to the toughness, flexibility and thermal stability of ethylene vinyl acetate (EVA) nanocomposites - Tuty Fareyhynn Mohammed Fitri (School of Materials Engineering, 2015)
The main objective of this study was to produce flexible and tough EVA nanocomposite by incorporating pre-dispersed organically modified montmorillonite (organo-MMT) for use in biomedical applications. The three specific objectives were to investigate the efficiency of toluene and water as pre-dispersing medium of organo - MMT nanofiller in order to enhance toughness, flexibility and thermal stability of EVA nanocomposite; to compare two types of pre-dispersing methods which were; magnetic stirring and ultrasonication to the chemistry of the organo-MMT nanofiller and subsequent EVA nanocomposite toughness, flexibility and thermal stability; to compare the effects of pre-dispersing time (2 and 5 minutes) to the toughness, flexibility and thermal stability of the EVA nanocomposite.